Diastolic Dysfunction With Preserved Ejection Fraction After the Fontan Procedure - Chowdhury, Shahryar M.; Graham, Eric M.; Taylor, Carolyn L.; Savage, Andrew; McHugh, Kimberly E.; Gaydos, Stephanie; Nutting, Arni C.; Zile, Michael R.; Atz, Andrew M. (Journal of the American Heart Association, 2022)
Background Heart failure phenotyping in single-ventricle Fontan patients is challenging, particularly in patients with normal ejection fraction (EF). The objective of this study was to identify Fontan patients with abnormal diastolic function, who are high risk for heart failure with preserved ejection fraction (HFpEF), and characterize their cardiac mechanics, exercise function, and functional health status. Methods and Results Data were obtained from the Pediatric Heart Network Fontan Cross-sectional Study database. EF was considered abnormal if <50%. Diastolic function was defined as abnormal if the diastolic pressure:volume quotient (lateral E:e'/end-diastolic volume) was >90th percentile (≥0.26 mL ). Patients were divided into: controls=normal EF and diastolic function; systolic dysfunction (SD) = abnormal EF with normal diastolic function; diastolic dysfunction (DD) = normal EF with abnormal diastolic pressure:volume quotient. Exercise function was quantified as percent predicted peak VO . Physical Functioning Summary Score (FSS) was reported from the Child Health Questionnaire. A total of 239 patients were included, 177 (74%) control, 36 (15%) SD, and 26 (11%) DD. Median age was 12.2 (5.4) years. Arterial elastance, a measure of arterial stiffness, was higher in DD (3.6±1.1 mm Hg/mL) compared with controls (2.5±0.8 mm Hg/mL), <0.01. DD patients had lower predicted peak VO compared with controls (52% [20] versus 67% [23], <0.01). Physical FSS was lower in DD (45±13) and SD (44±13) compared with controls (50±7), <0.01. Conclusions Fontan patients with abnormal diastolic function and normal EF have decreased exercise tolerance, decreased functional health status, and elevated arterial stiffness. Identification of patients at high risk for HFpEF is feasible and should be considered when evaluating Fontan patients.